KEMAMPUAN PENALARAN ADAPTIF SISWA DIKAJI DARI GAYA KOGNITIF DALAM MATERI SEGIEMPAT DI SMP - Arnika, Ika; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe background in this research is the student’s adaptive reasoning ability that is still relatively low. Adaptive reasoning ability are influenced by some factors,  one of them is student’s cognitive style. Therefore, adaptive reasoning ability should be analyzed based on student’s cognitive style. This research aims to describe the student’suu adaptive reasoning ability based on cognitive style in quadrilateral at SMP Negeri 8 Pontianak. The research method use descriptive method with case study. The subject in this research are four students grade VIII D consist of two reflective cognitive style students and two impulsive cognitive style students. The result of data analysis showed that the adaptive reasoning ability are different depending on their cognitive style.  One of students who has reflective cognitive style can  fulfill five indicator of adaptive reasoning ability and one of other students who has reflective cognitive style can  fulfill four indicator of adaptive reasoning ability. One of students who has impulsive cognitive style can  fulfill four indicator of adaptive reasoning ability and one of other students who has impulsive cognitive style can  fulfill two indicator of adaptive reasoning ability.  Keywords: Adaptive Reasoning Ability, Cognitive Style, Quadrilateral